Collagen VII half-life at the dermal-epidermal junction zone: implications for mechanisms and therapy of genodermatoses - Kühl, Tobias Hans-Jürgen; Haußer-Siller, Ingrid (The journal of investigative dermatology, 2016)
The tissue half-life of proteins largely determines treatment frequency of non-gene-editing-based therapies targeting the cause of genodermatoses. Surprisingly, such knowledge is missing for a vast number of proteins involved in pathologies. The dermal-epidermal junction zone is believed to be a rather static structure, but to our knowledge no detailed analysis of the stability of proteins within this zone has been performed. Here, we addressed the in vivo half-life of collagen type VII using genetic ablation of its expression and therapeutic introduction of exogenous collagen VII in a preclinical model. A similar in vivo stability of collagen VII was observed in the skin, tongue, and esophagus, with a half-life of about 1 month. Collagen VII expressed by intradermally injected mesenchymal stromal cells also exhibited a similar half-life. Our study provides key information needed for the development of protein replacement or cell-based therapies for dystrophic epidermolysis bullosa caused by genetic deficiency of collagen VII. Moreover, by showing what we define as an intermediate half-life of collagen VII, our study challenges the view of the dermal-epidermal junction zone as a static structure with very slow turnover.
Gesehen am 04.09.2019